Cancer in the offspring of fathers in hydrocarbon-related occupations. Issue 2 (June 1976) - Hakulinen, T; Salonen, T; Teppo, L
Abstract : A case-control study has been conducted to see whether a hydrocarbon-related occupation of the father at the time of conception constitutes a risk factor for malignant disease in the offspring. The series comprised 852 cancer cases from the Finnish Cancer Registry and 852 controls matched for date of birth and domicile. The father's occupation for both the cases and controls was ascertained from the records of antenatal clinics. No significant associations were found between the commonest types of childhood cancer and hydrocarbon-related occupations--that is, motor-vehicle mechanics, machinists, miners, painters, and motor-vehicle drivers. Risk ratio 2 was excluded from most of the 95% confidence intervals for children under 15 years of age. The results do not support the hypothesis that there is an excess risk of cancer in the children of fathers in hydrocarbon-related occupations.